Solution structure of propane and propene dissolved in the ionic liquid 1-butyl-3-methylimidazolium bis{(trifluoromethyl)sulfonyl}imide from neutron diffraction with H/D substitution and empirical potential structure refinement modelling. (17th November 2019) - Moura, Leila; Gilmore, Mark; Callear, Samantha K.; Youngs, Tristan G. A.; Holbrey, John D.
Abstract : Neutron scattering combined with H/D-isotopic substitution, fitting the experimental data using the Empirical Potential Structure Refinement (EPSR) method has been used to investigate the liquid structure of 1-butyl-3-methylimidazolium bis {(trifluoromethyl)sulfonyl}imide ( [ C 4 m i m ] [ N T f 2 ] ) and solutions of propane (0.15 mol fraction) and propene (0.23 mol fraction) dissolved in the ionic liquid dissolved after pressurising at 6 bar. Both strong cation-anion and cation-cation correlations are observed in the first coordination shell with anions and cations occupying mutually exclusive positions around the imidazolium cation, consistent with previous models derived from molecular dynamics simulation. No significant changes in the neutron scattering data were observed after dissolution of either propane and propene suggesting that the primary coulombic structure of the ionic liquid is preserved. Modelling the data with EPSR reveals subtle differences in the cation-hydrocarbon correlations, with propene associated with all three imidazolium ring C-H positions whereas propane exhibits less association with the C(2)-H ring position and has a greater level of correlation with the terminal − C H 3 group of the cation butyl-chain. GRAPHICAL ABSTRACT: